Peran Baitul Mal dalam Pemungutan Zakat Profesi Notaris di Kota Langsa - Maulina Ulfanur; Nur Anshari; Satria Darma (Sekolah Tinggi Ilmu Syariah (STIS) Ummul Ayman Pidie Jaya, Ace, 2023)
If someone's professional income has met the mandatory zakat provisions, it is obligatory for him to pay zakat. The problem in this paper is how the role of Baitul Mal in collecting zakat profession, especially zakat from the notary profession in Langsa City and what are the obstacles in collecting zakat professionally. notary in Langsa City. And here the author wants to reveal the extent of the role of Baitul Mal in collecting zakat on notaries in Langsa City. This type of research is qualitative research. To collect the data needed in this study, the authors used Field Research, namely by using several data collection techniques, namely interviews and documentation. Based on the research that has been carried out at the Baitul Mal Kota Langsa office, the authors can conclude. So far, Baitul Mal Kota Langsa is still not optimal in socializing professional zakat to Notaries in Langsa City. So that there are still many who do not understand that they can channel their professional zakat to mustahiq zakat through the City Baitul Mall. However, so far, Baitul Mal has actually provided information and outreach to the public, but mostly in the form of lectures and billboards.